A Detailed Numerical Study of NOx Kinetics in Counterflow Methane Diffusion Flames: Effects of Fuel-Side versus Oxidizer-Side Dilution. (3rd March 2021) - Xu, Huanhuan; Liu, Fengshan; Wang, Zhiqiang; Ren, Xiaohan; Chen, Juan; Li, Qiang; Zhu, Zilin
Abstract : Dilution combustion has been widely utilized due to various merits, such as enhanced efficiency, fewer pollutants emissions, and even a promising future in alleviating global warming. Diluents can be introduced through the oxidizer or fuel side to achieve the desired combustion properties, and H2 O and CO2 are the most common ones. A comprehensive comparison between the different dilution methods still lacks understanding and optimizes the dilution combustion technologies. This study numerically compared the effects of H2 O and CO2 dilution in the oxidizer or fuel stream on counterflow methane diffusion flames, emphasizing NO formation kinetics. Results showed that the impact of different radiation heat transfer models on NO emissions diminishes with increasing the dilution ratio. The calculations of radiation heat transfer were treated in three ways: radiation-neglected, optically thin, and using a nongrey radiation model. When keeping the oxygen content and methane fraction constant, CO2 dilution in the air-side has the most profound influence on NO reduction, and CO2 dilution in the fuel-side has the least. H2 O dilution showed a medium impact with a larger degree on air-side than that on fuel-side. To gain a deeper understanding of this effect order, the contributions of different NO formation routes were quantified, and analyses were made based on the diluents' chemical and thermal effects. It was found that the oxidizer-side dilution and fuel-side dilution affect the NO formation pathway similarly. Still, the influence of H2 O dilution on the NO formation pathway differs from that of CO2 dilution.